Cardioprotective Activity of Polyphenolic Extract of Tubers of Cyperus Rotundus and Taurine against Isoproterenol - induced Myocardial Infraction in Rats: Troponin-I and Histological Findings - Alyaa Majid (Journal of Global Pharma Technology, 2018)
Objective: The polyphenolic extract of tuberus of cyperus rotundus and taurine was studied for the cardio protective activity using isoproterenol induced myocardial infraction in female rats. Materials and Methods: Sixty of female rats (Rattus norvegicus) were used in the present study. Animals were divided into 10 groups ( 6 for each group). MI was induced in rats with ISO (85 mg/kg) twice at an interval of 24 hrs. ISO produced significant alterations in the troponin-I and necrosis in the heart. The effect of polyphenolic extract of tuberus of cyperus rotundus oral treatment for 21 days at two doses (15 mg and 30 mg/kg, body weight) and taurine at two doses (100 mg and 200 mg/kg, body weight) was evaluated against ISO- induced cardiac necrosis. Results: Significant myocardial necrosis and increase in serum levels of troponin-I were observed in ISO- treated animals as compared with the normal control animals. Polyphenolic extract of tubers of cyperus rotundus and taurine showed a significant cardio protective activity by lowering the levels of serum troponin-I and less myocardial necrosis. Conclusion: These findings the synergistic cardio protective effects of polyphenolic extract of tubers of cyperus rotundus and taurine during ISO-induced myocardial infraction in rats.Keywords: Isoproterenol, Cardiac troponin I, Myocardial necrosis, Histology, Cyperus rotundus, Taurine.